2016
DOI: 10.1186/s40604-016-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the vision of entrepreneurial universities: a case study of UNIRIO in Brazil

Abstract: This paper aims to study a set of entrepreneurial activities at a public university and the interaction with other universities, the business sector and government at Federal University of the State of Rio de Janeiro (UNIRIO), Brazil. The study sought an understanding of the dynamics and results of the research activities, the interaction with various organizations and the establishing of commercial, social, cultural and civic entrepreneurship developed by UNIRIO's research groups. Analysis of the activities r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Policies on intellectual property are built into HEI's protocols which is important to nurture innovation and give support to companies that can develop and employ people. The development of entrepreneurial activities incorporating a third mission proved to be a complex matter (Almeida et al, 2016). Almeida et al (2016) showed that when commercial entrepreneurship was beginning and when patenting, technology transfer, and spin-offs were new and untested, although embodied in university proposals, it was difficult to see the evidence in practice.…”
Section: Need For New Roles For Higher Education Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies on intellectual property are built into HEI's protocols which is important to nurture innovation and give support to companies that can develop and employ people. The development of entrepreneurial activities incorporating a third mission proved to be a complex matter (Almeida et al, 2016). Almeida et al (2016) showed that when commercial entrepreneurship was beginning and when patenting, technology transfer, and spin-offs were new and untested, although embodied in university proposals, it was difficult to see the evidence in practice.…”
Section: Need For New Roles For Higher Education Institutionsmentioning
confidence: 99%
“…The development of entrepreneurial activities incorporating a third mission proved to be a complex matter (Almeida et al, 2016). Almeida et al (2016) showed that when commercial entrepreneurship was beginning and when patenting, technology transfer, and spin-offs were new and untested, although embodied in university proposals, it was difficult to see the evidence in practice. Change takes time and investment.…”
Section: Need For New Roles For Higher Education Institutionsmentioning
confidence: 99%
“…To be qualified as entrepreneurial, universities should develop different strategies through a thorough transformative process: "(1) the university starts to define its priorities and diversify its income sources, (2) the institution starts commercializing the intellectual property that arises from its research activities, and (3) the university takes an active role in participating in its regional innovation environment" (Etzkowitz, 2015, p. 63; see also Almeida et al, 2016).…”
Section: Review Of European Studiesmentioning
confidence: 99%
“…Dentre alguns dos trabalhos já realizados no Brasil que se concentram no estudo do tema "universidade empreendedora" (Almeida et al, 2016;Andrade, 2014;Camargo, 2015;Casado, Siluk & Zampieri, 2012;Guaranys, 2006;Lorentz, 2015;Morgades, 2016;Orsett, 2016;Otani, 2008;Rothenbuhler, 2000;Sá, 2014;Souza & Palma, 2010), os mesmos se destacam por abordar e defender positivamente a sua importância. Portanto, ressalta-se a relevância em lançar um novo olhar para o tema proposto a partir da já mencionada associação entre universidade empreendedora e empresarização, bem como por trabalhar o tema a partir de um viés crítico.…”
Section: Empresarização Neoliberalismo Estado E O Discurso Da Univeunclassified